Strongly entangled light from planar microcavities - Pagel, D.; Fehske, H.; Sperling, Jan; Vogel, W. (Physical Review A)

Analytical progress on symmetric geometric discord: Measurement-based upper bounds - Miranowicz, Adam; Horodecki, Paweł; Chhajlany, Ravindra W.; Tuziemski, Jan; Sperling, Jan (Physical Review A)

True photocounting statistics of multiple on-off detectors - Sperling, Jan; Vogel, W.; Agarwal, G. S. (Physical Review A)

Multiphoton state engineering by heralded interference between single photons and coherent states - Bartley, Tim; Donati, Gaia; Spring, Justin B.; Jin, Xian-Min; Barbieri, Marco; Datta, Animesh; Smith, Brian J.; Walmsley, Ian A. (Physical Review A)

Limits on the deterministic creation of pure single-photon states using parametric down-conversion - Christ, Andreas; Silberhorn, Christine (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Determination of the Schmidt number - Sperling, Jan; Vogel, W. (Physical Review A)

High-performance single-photon generation with commercial-grade optical fiber - Söller, Christoph; Cohen, Offir; Smith, Brian J.; Walmsley, Ian A.; Silberhorn, Christine (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Bridging visible and telecom wavelengths with a single-mode broadband photon pair source - Söller, C.; Brecht, Benjamin; Mosley, P. J.; Zang, L. Y.; Podlipensky, A.; Joly, N. Y.; Russell, P. St. J.; Silberhorn, Christine (Physical Review A)

Nonlocal Talbot self-imaging with incoherent light - Luo, Kai Hong; Chen, Xi-Hao; Liu, Qian; Wu, Ling-An (Physical Review A)

Verifying continuous-variable entanglement in finite spaces - Sperling, Jan; Vogel, W. (Physical Review A)

Representation of entanglement by negative quasiprobabilities - Sperling, Jan; Vogel, W. (Physical Review A)

Necessary and sufficient conditions for bipartite entanglement - Sperling, Jan; Vogel, W. (Physical Review A)

Indirect spin dephasing via charge-state decoherence in optical control schemes in quantum dots - Grodecka, A.; Machnikowski, P.; Förstner, Jens (Physical Review A)
We demonstrate that an optically driven spin of a carrier in a quantum dot undergoes indirect dephasing via conditional optically induced charge evolution even in the absence of any direct interaction between the spin and its environment. A generic model for the indirect dephasing with a three-component system with spin, charge, and reservoir is proposed. This indirect decoherence channel is studied for the optical spin manipulation in a quantum dot with a microscopic description of the charge-phonon interaction taking into account its non-Markovian nature.
Keywords: tet_topic_qd

Role of multiphoton bunching in high-order ghost imaging with thermal light sources - Liu, Qian; Chen, Xi-Hao; Luo, Kai Hong; Wu, Wei; Wu, Ling-An (Physical Review A)

Second-order Talbot effect with entangled photon pairs - Luo, Kai Hong; Wen, Jianming; Chen, Xi-Hao; Liu, Qian; Xiao, Min; Wu, Ling-An (Physical Review A)

Signatures of nonclassicality in mixed-state quantum computation - Datta, Animesh; Gharibian, Sevag (Physical Review A)
We investigate signatures of non-classicality in quantum states, in particular, those involved in the DQC1 model of mixed-state quantum computation [Phys. Rev. Lett. 81, 5672 (1998)]. To do so, we consider two known non-classicality criteria. The first quantifies disturbance of a quantum state under locally noneffective unitary operations (LNU), which are local unitaries acting invariantly on a subsystem. The second quantifies measurement induced disturbance (MID) in the eigenbasis of the reduced density matrices. We study the role of both figures of non-classicality in the exponential speedup of the DQC1 model and compare them vis-a-vis the interpretation provided in terms of quantum discord. In particular, we prove that a non-zero quantum discord implies a non-zero shift under LNUs. We also use the MID measure to study the locking of classical correlations [Phys. Rev. Lett. 92, 067902 (2004)] using two mutually unbiased bases (MUB). We find the MID measure to exactly correspond to the number of locked bits of correlation. For three or more MUBs, it predicts the possibility of superior locking effects.

Electric-field effects on nematic droplets with negative dielectric anisotropy - Xu, F.; Kitzerow, Heinz-Siegfried; Crooker, P. P. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Dynamics of blue-phase selective reflections in an electric field - Kitzerow, Heinz-Siegfried; Crooker, P. P.; Kwok, S. L.; Xu, J.; Heppke, G. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics